DEVELOPING REFLECTIVE PRACTICE AS PART OF TEACHER TRAINING WITH THE USE OF CRITICAL INCIDENTS - Kossakowska-Pisarek, Sylwia (Neofilolog, 2020)
Preparing thoughtful reflective practitioners has become a common concept in the teacher education literature. Prior educational experiences offer excellent opportunity for students to reflect on authentic teaching examples and provide constructive ways to engage in reflective practice. This study examines critical incidents as a tool for developing reflective thinking skills among teacher trainees (N=11). The research on use of critical incidents for training comprised a questionnaire and group discussions. The instrument used for analyzing critical incidents included personal details, factual information and open-ended questions concerning reasons for and consequences of the incident, associated emotions, reflections connected with it, lessons from this incident and its implications for the future. Overall, although some crucial issues arose, the technique proved useful for training, and was assessed as positive and valuable by the teacher trainees. Some pedagogical implications were formulated regarding problems with understanding the notion of critical incident, previous training of the teacher trainees and the need for a supportive environment.